Ekstraksi Topik Pantun di Twitter Menggunakan K-Means Clustering - Ulinnuha, Nurissaidah; Indriyani, Jiphie Gilia (KUBIK, 2023)
Pantun is an old form of poetry in Indonesia. Over time, the anxiety of the existence of rhymes in society has become the anxiety of literary, language and cultural activists. This study aims to explore the existence of the use of rhymes on social media which was highly encouraged by young people in the era of Society 5.0. There are two types of rhymes studied, namely general and islamic rhymes. The method used is K-Means clustering analysis to find rhyme topics that are often used in social media. The general category of pantun cluster structure belongs to the weak structure because the silhouette coefficient values are in the range of 0.26-0.5 while the Islamic pantun group structure belongs to the good too strong structure because the silhouette coefficient values are in the range of 0.4-0.9. It was found that the general category of rhymes were still widely used on social media with the type of theme being youth rhymes. The purpose of using the rhyme is more dominant to express feelings. On the other hand, the islamic category of rhymes is rarely used on social media with the type of theme being parental rhymes. The purpose of using the rhyme is more dominant to religious symbols.